Konsep Profit Dalam Perspektif Islam - Suci Ramadhana; Suci Ramadhini (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2023)
Profit is also known as profit or Profit. One of the most fundamental aspects of trade is profit, which is obtained through the redistribution of resources. In Islam, there is a lot of emphasis on making money and using resources. In Islam, the concept of profit is based on the principles of love, blessing, sincerity, and accepting existing risks. This study was conducted with the intention to illustrate the concept of “profit” from an Islamic perspective. Qualitative research methods and various secondary sources were used to collect data for the study. Syntactic, semantic and pragmatic analysis all point to the same place in the framework of accounting theory where the concept of profit is located. syntactically, as in the rules that define it; semantically, as in relation to the underlying economic reality; and pragmatically, as in the use of concepts by investors who are aware of their meaning and use them regardless of how they are measured.